About case studies and experience reports - Lopes, Marcos Venícios de Oliveira (Rev Rene, 2012)
The quality of the scientific production of a researcher has often been assessed by the insertion and international impact factors. Although it is open to criticism, this is the posture currently adopted in Brazil and in other countries. In addition, the journals responsible for the dissemination of these results develop their own strategies that enable their inclusion in international databases. These criteria include, among other things, the type of article published, preferring those from field research and that create scientific evidences of high level.DOI:https://doi.org/10.15253/2175-6783.2012000400001